Design and development of a rack and pinion steering system for F1 cart - Mohd Zahiri Mohd Amin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
This is study of rack and pinion streering system that replace the axisting direct linkage streering system on SMaRT (Sachool of manufacturing Racing Team) F1 cart. This reports includes the study of the potential for developing an upgrade of streeing system which is new design of rack and pinion This also improving rack and pinion steering system for better use on F1 cart. A virtual prototype of rack and pinion steering gear and FEA (Finite Element Analisys) are made in SolidWork softwere. The FMEA (Failure Mode And Effect Analisys) is also being us to determine the failure of new rack and pinion design.